Representations of work engagement and workaholism in modern psychological research - Valentina V. Barabanshchikova; Oxana A. Klimova (Национальный психологический журнал, 2015)
The paper provides an overview of work engagement and workaholism, and also the current research. Work engagement differs from workaholism as a psychological phenomenon, but both concepts are closely connected with each other. The scientific research of the phenomena mentioned above began only in 1970, when Oates published his first book called “On being a “workaholic”. Each employee has to find balance between private life and work to get utmost job satisfaction, and to perform his/her job responsibilities productively. Work engaged staff have higher levels of subjective comfort and psychological well-being, without any experience of occupational deteriorations. In modern psychology, there is no prescription for perfect recipe of finding balance between work and family that entails different angles of considering work engagement and workaholism, their causes and prevention mechanisms. On the other hand, the impact of excessive work engagement may be one of the reasons of developing negative human functional states that plays a moderating role in the transit stage from work engagement to workaholism. Schaufeli discribed work engagement as a positive, affective-motivational state of fulfillment that can be characterized by vigor, dedication, and absorption. Workaholism is a multidimensional construct, which can be linked to both positive and negative outcomes. At the contemporary stage of scientific development a lot of difficulties in studying workaholism and work engagement could be analyzed, e.g. there are no adopted Russian diagnostics instruments to assess workaholism and its manifastations. Thus, further research should be devoted to the issues of choosing proper research instruments in order to obtain clear and reliable results.